Didactics and evaluation in professional practices. Challenges for university education training of social work career - Anabalón Anabalón, Yasna Belén (2025)
Objective: This study analyzes practical, didactic, and evaluative experiences in the context of university professional practice, drawing on the narratives of 47 students (from initial, intermediate, and final internships) and 9 tutor-teachers from two campuses of a state university in southern Chile. Method: Data were collected through discussion groups guided by a thematically validated script and analyzed using structural analysis, applying a parallel structure in the form of binary discourse. Results: The findings show that tutor-teacher supervision promotes dialogic learning and that the emotional dimension is a central component of student–teacher interactions. In addition, the portfolio of evidence emerges as the most widely used didactic and evaluative resource in the training process. Discussion: Student narratives reveal tensions related to the outdated knowledge of some tutor-teachers in relation to current professional contexts and challenges, which may affect the relevance and quality of the training provided.